2020
DOI: 10.1093/ve/veaa037
|View full text |Cite
|
Sign up to set email alerts
|

Co-circulation of both low and highly pathogenic avian influenza H5 viruses in current poultry epidemics in Taiwan

Abstract: Highly pathogenic avian influenza (HPAI) A(H5) viruses belonging to clade 2.3.4.4c of the A/goose/Guangdong/1/96-like (Gs/GD) lineage caused severe global outbreaks in domestic birds from 2014 to 2015, that also represented the first incursions of Gs/GD viruses into Taiwan and the USA. However, few studies have investigated the circulation of clade 2.3.4.4c viruses after 2015. Here, we describe Gs/GD clade 2.3.4.4c and Mexican-like H5N2 viruses that were isolated in Taiwan during active surveillance conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…In particular, a new re-assorted HPAI H5N5 with HA gene belonging to clade 2.3.4.4 descendent with Taiwan local strains, was identified since September, 2019. Thirdly, our viral sequencing data from the field collections during 2019 provided the directly scientific support of gene exchange between the domestic poultry and wild birds [ 53 ]. Fourth, avian influenza virus monitoring in migratory birds has been performed in Taiwan since 1998 and was recently expanded to include the dead wild birds collected by the citizen scientists [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a new re-assorted HPAI H5N5 with HA gene belonging to clade 2.3.4.4 descendent with Taiwan local strains, was identified since September, 2019. Thirdly, our viral sequencing data from the field collections during 2019 provided the directly scientific support of gene exchange between the domestic poultry and wild birds [ 53 ]. Fourth, avian influenza virus monitoring in migratory birds has been performed in Taiwan since 1998 and was recently expanded to include the dead wild birds collected by the citizen scientists [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, Li et al (2020) also reported codetection in March 2019 of another A(H5N2) virus on the same farm as one of the above described novel reassortant HPAI A(H5N2) viruses. This virus belonged for all its gene segments to the Mexican-like LPAI A(H5N2) virus lineage, recurrently detected in Taiwan since 2003 and responsible for the emergence in 2012 of a directly related HPAI virus.…”
Section: Detectionsmentioning
confidence: 71%
“…For this same genotype, the polymerase gene segments were derived from a Eurasian LPAI virus gene pool for PB2 and PA, and from a north American LPAI virus gene pool for PB1. Whereas, for the genotype detected in March 2019, all internal gene segments (except M) were distinct from known A(H5) virus sequences detected in Taiwan, but clustered with other Eurasian LPAI viruses.In the same study,Li et al (2020) also reported codetection in March 2019 of another A(H5N2) virus on the same farm as one of the above described novel reassortant HPAI A(H5N2) viruses. This virus belonged for all its gene segments to the Mexican-like LPAI A(H5N2) virus lineage, recurrently detected in Taiwan since 2003 and responsible for the emergence in 2012 of a directly related HPAI virus.…”
mentioning
confidence: 71%
See 2 more Smart Citations